What Drives The Success of Rural Development? Evidence from West Java, Indonesia - Ramadhani, Fahmi; Adi Saputra, Putu Mahardika (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
Success in rural development lies in identifying and developing the appropriate factors to make development work. Finding the best way to achieve successful rural development is a question that is currently difficult to answer. This study aims to identify the factors that can influence the success of village development, by focusing on the variables contained in each dimension of the Village Development Index (IDM), namely the dimensions of social resilience, economic resilience, environmental resilience, and village fiscal independence. This study focuses on the conditions of 5,312 villages in West Java Province, Indonesia. The data in this study is obtained from the Village Potential (Podes) 2019 micro data and Village Development Index 2020 by conducting descriptive statistical analysis and multiple linear regression analysis. The results show that sustainable development in villages can be achieved by ensuring the availability of village social infrastructure, and increasing the effectiveness of village economic institutions. In addition, the government needs to ensure the focused and strategic development plans so that village revenue can be efficiently utilized for development. These factors must be utilized by all village communities in order to avoid conflicts that occur in the village.